Financing higher education : current patterns - (:unkn) unknown (My University, 1990)
"This report discusses the nature of the changes in the patterns of financing and control of higher education systems which have been observed in OECD countries over the last decade. In particular, it analyses the links between expenditure patterns, costs and efficiency in higher education in relation to the mechanisms by which institutions receive funds, and against the background of changing policies for public financing." (author's abstract) ((en)) Der Report beschreibt und diskutiert die Finanzierungsmuster und die Kontrollmechanismen der Bildungssysteme in den OECD-Ländern, die in der letzten Dekade analysiert wurden. (IAB2)
Finanzierung des Hochschulsystems - Aktuelle Muster
Keywords: S 1.4 Hochschulbildung; S 4 Kosten & Finanzierung; Stipendium; Bildungsförderung; Entwicklung; Hochschulsystem; Finanzierung; Quantitative Angaben